Stem cell origin differently affects bone tissue engineering strategies - Mattioli-Belmonte, Monica; Teti, Gabriella; Salvatore, Viviana; Focaroli, Stefano; Orciani, Monia; Dicarlo, Manuela; Fini, Milena; Orsini, Giovanna; Di Primio, Roberto; Falconi, Mirella (Frontiers in Physiology, 2015)
Bone tissue engineering approaches are encouraging for the improvement of conventional bone grafting technique drawbacks. Thanks to their self-renewal and multi-lineage differentiation ability, stem cells are one of the major actors in tissue engineering approaches, and among these adult mesenchymal stem cells (MSCs) hold a great promise for regenerative medicine strategies. Bone marrow MSCs (BM-MSCs) are the first- identified and well-recognized stem cell population used in bone tissue engineering. Nevertheless, several factors hamper BM-MSC clinical application and subsequently, new stem cell sources have been investigated for these purposes. The fruitful selection and combination of tissue engineered scaffold, progenitor cells, and physiologic signaling molecules allowed the surgeon to reconstruct the missing natural tissue. On the basis of these considerations, we analyzed the capability of two different scaffolds, planned for osteochondral tissue regeneration, to modulate differentiation of adult stem cells of dissimilar local sources (i.e., periodontal ligament, maxillary periosteum) as well as adipose-derived stem cells (ASCs), in view of possible craniofacial tissue engineering strategies. We demonstrated that cells are differently committed toward the osteoblastic phenotype and therefore, taking into account their specific features, they could be intriguing cell sources in different stem cell-based bone/periodontal tissue regeneration approaches.